Synchronised capacitor discharge in the management of cardiac arrhythmias with particular reference to the haemodynamic significance of atrial systole - Resnekov, Leon Zundel (Department of Medicine, 2020)
In December 1962 a boy of 15 years was referred to the National Heart Hospital because of a ventricular tachycardia, which had proved resistant to treatment with procaine amide, quinidine, atropine, prostigmine, prednisone and digoxin. A second stage, total correction for tetralogy of Pallot had been successfully performed two years before by Sir Russell Brock and the tachycardia followed a sudden blow on the cheat at his school. Further drug treatment to the point of toxicity proved equally unavailing and ten days after the onset of the arrhythmia severe congestive heart failure was present.